Food safety in Peruvian food restaurants for entrepreneurs - Paucar Luna, Jorge; Vásquez-Pajuelo, Lida; Navarrete Ormeño , Mayra Elizabeth (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
The gastronomic boom in Peru has motivated many entrepreneurs to invest in Peruvian food restaurants; hoping that when the Peruvian State declares it a cultural heritage of the nation, the legal standards of quality and safety will be implemented. In this sense, it should be range from the opening and operation of new premises and that emphasis be placed on clear regulations for micro and medium enterprises. The objective of this research was to design quality and safety measures focused on protecting the life and health of diners in the food preparation process in small and medium-sized Peruvian foodrestaurants. The methodology used is qualitative, whose result of the analysis of the decision tree determined the Critical Control Points (CCP) being cooking and disinfection stages that control biological hazards. It was concluded, in improving cost performance, through the control of losses in the storage of raw materials and rejection of preparations, at the same time, it is important ensuring consumer protection, providing safe food, that generate trust and satisfaction.